2014
DOI: 10.1002/asia.201301695
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Template‐Free Synthesis of NaYF4 Upconversion Hollow Nanospheres for Bioimaging and Drug Delivery

Abstract: Hollow-structured nanomaterials with fluorescent properties are extremely attractive for image-guided cancer therapy. In this paper, sub-100 nm and hydrophilic NaYF4 upconversion (UC) hollow nanospheres (HNSs) with multicolor UC luminescence and drug-delivery properties were successfully prepared by a facile one-pot template-free hydrothermal route using polyetherimide (PEI) polymer as the stabilizing agent. XRD, SEM, TEM, and N2-adsorption/desorption were used to characterize the as-obtained products. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…PEI, a commonly used surface modification agent, was chosen to modify the surface of UCNPs. Hence, the PEI‐modified NaYF 4 :Yb,Er UCNPs (PEI‐UCNPs) were synthesized by a modified one‐step solvothermal method . The SEM ( Figure a) and transmission electron microscopes (TEM) images (inset in Figure a) clearly reveal that the UCNPs are spherical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEI, a commonly used surface modification agent, was chosen to modify the surface of UCNPs. Hence, the PEI‐modified NaYF 4 :Yb,Er UCNPs (PEI‐UCNPs) were synthesized by a modified one‐step solvothermal method . The SEM ( Figure a) and transmission electron microscopes (TEM) images (inset in Figure a) clearly reveal that the UCNPs are spherical.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, NPs may undergo transformations in a plant system, which will modify their ultimate toxicity and behavior in plants. For example, Zhang et al reported that RE oxide NPs (La 2 O 3 , Yb 2 O 3 , and CeO 2 ) were transformed into RE phosphates with the assistance of root‐exuded organic acids and reducing substances, which affected the phytotoxicity and behavior of NPs . NaYF 4 , as one of the most effective upconversion luminescent nanomaterials, there are few reports about the toxicity effect of NaYF 4 UCNPs on plants .…”
Section: Introductionmentioning
confidence: 99%
“…50 As an example, Li reported an e±cient, one-pot route for synthesizing sub-100 nm hydrophilic NaYF 4 -based upconversion hollow nanospheres in hydrothermal condition. 51 …”
Section: One-pot Template-free Synthesismentioning
confidence: 99%
“…Non-invasive imaging has become a useful tool for bioimaging, detection and medical diagnosis. [1][2][3][4][5][6][7][8] To date, lots of non-invasive imaging techniques, including uorescence imaging, 9 magnetic resonance imaging (MRI), 10 X-ray computed tomography (CT), 11 positron emission tomography (PET), 4,11,12 single-photon emission computed tomography (SPECT) 12 and photoacoustic tomography (PAT), 13,14 have been developed. As every single technique has its own limits (e.g., spatial resolution, imaging depth and scanning speed), developing multimodal noninvasive imaging is of great importance to combine the merits of individual imaging techniques.…”
Section: Introductionmentioning
confidence: 99%